Potential transfer of endotoxin across high-flux polysulfone membranes. - Bommer, Jürgen; Becker, Klaus-Peter; Urbaschek, Renate (Journal of the American Society of Nephrology, 1996)
It has been postulated that synthetic membranes, such as polysulfone membranes, are rather impermeable for endotoxin or endotoxin fragments and can be used for sterile filtration of dialysate. It has never been investigated, however, whether endotoxin permeability may be different in commercially available polysulfone membranes. In vitro, we found a significantly different permeability for endotoxin in two standard dialyzers and one test dialyzer with high-flux polysulfone membranes. In contrast to the F-60 dialyzer with a very low permeability for endotoxin, a stepwise increasing load of endotoxin concentration in the dialysate compartment of the PN 1913 test dialyzer and Primus 1350 polysulfone dialyzer was followed by a stepwise increase of endotoxin in the blood compartment. A significant transfer across the membranes was found when the endotoxin concentration in the dialysate compartment was > 10 ng/mL in the PN 1913 and > 0.5 ng/mL in the Primus 1350. In the latter, about 0.5% of the endotoxin concentration of the dialysate compartment was found in the blood compartment. The data suggest that manufacturers have to evaluate the performance and other properties of their synthetic membranes in detail.